Analyzing and conceptualizing Pakistan’s pioneering disaster risk communication Mobile application: a case study of PDMA Madadgar - Jan, Mushtaq Ahmad; Ullah, Syed Irfan; Ullah, Waheed; Ullah, Safi; Tariq, Hisham; Fernando, Terrence; Ali, Amjad; Rahman, Zahid Ur (Frontiers in Communication, 2025)
Pakistan’s vulnerability to disasters necessitates effective disaster risk communication. This study presents a conceptual model of the PDMA Madadgar Application (hereinafter Madadgar) for subsequent code development and testing. Employing the design science research approach, data were collected through in-depth interviews from the purposefully selected sample participants and analyzed through the content analysis method. Our findings highlight the conceptualization of the app and the strengths it provides in real-time disaster alerts, early warnings and critical information dissemination. The data reveals that the model is highly interactive. A major stake has been provided to the local communities and field-based staff to receive and disseminate early warning messages, locate evacuation centers, report disasters without warning, and digitally conduct damage assessment. This study enhances disaster risk communication in Pakistan and informs the global development of effective mobile-based solutions. Maddagar is Pakistan’s pioneer interactive Android-based disaster risk communication app for communities in Pakistan. Madadgar directly contributes to the local implementation of Pakistan’s National Disaster Management Act 2010 and National Disaster Risk Reduction Policy-2013 as well as the Sendai Framework for Disaster Risk Reduction and the Sustainable Development Goals. While the current Madadgar model is specifically designed for use within the Khyber Pakhtunkhwa province of Pakistan, reflecting the decentralization of disaster risk reduction to the provinces following the 18th constitutional amendment, its underlying principles and architecture offer a scalable blueprint for adaptation and replication in other provinces and similar contexts.